LEAF COMPOST EDUCATION PROGRAM: A SOLUTION TO ORGANIC WASTE PROBLEMS IN CARANGWULUNG VILLAGE: PROGRAM EDUKASI KOMPOS DAUN, SOLUSI PERMASALAHAN SAMPAH ORGANIK DI DESA CARANGWULUNG - Wardani, Ratnaningtyas Wahyu Kusuma; Zulfa, Vivi Rodliyatuz; Damayanti, Ratih (Darmabakti Cendekia: Journal of Community Service and Engagements, 2025)
Background: Leaf litter in Carangwulung Village, Wonosalam, Jombang, often accumulates and is either burned or discarded, potentially contributing to air pollution and environmental degradation. Processing leaf waste into compost is an appropriate and practical solution that is not yet widely known or implemented by the local community. Objective: This activity aimed to improve the knowledge and skills of the community, particularly farmer groups, in independently managing dry leaf waste into compost fertilizer. Method: The methods used included education, outreach, and training involving 20 participants representing farmer groups. Evaluation was conducted using pre- and post-test questionnaires to assess knowledge levels, as well as direct observation during practical sessions and group discussions to assess participant skills. Results: There was an increase in participants' knowledge, with the average overall score rising from 7.5 on the pre-test to 9.0 on the post-test. Conclusion: This training successfully enhanced the community’s capacity in managing organic waste and represents an initial step toward adopting simple technologies to support environmentally friendly farming at the village level.